Condylar Agenesis: A Rare Case Report - Agarwal, Shakti; Kiran, Kamini; Kumar, Shailesh; Singh, Rameshwar; Das, Gourab (International Journal of Innovative Research in Medical Science, 2016)
Condylar agenesis is a rare case involving development, growth and aesthetic of face as well as dentition development and occlusal problems. In the absence of any long term study and shortage of subject material, management protocol of problems associated with agenesis of condyle vary from institute to institute and there is no internationally accepted protocol for the same. We are presenting a case of unilateral condylar agenesis with severe malocclusion that has never been published before. Subject in discussion is a 25 year old boy with agenesis of left condyle and perfectly normal right side condyle resulting in deviation towards left side of face.